Integrasi Pendidikan Karakter Dalam Pembelajaran Bahasa Arab di MAS Al-Hikmah Bandar Lampung - Ajeng Rahmawati, Rima; Muhammad Irham; Angger Putri Mahardini; Hadiyin Rifai; Angga Predi (STIT Darul Fattah Bandar Lampung, 2023)
MAS Al-Hikmah is one of the pioneers on Islamic educational institutions in Bandar Lampung which is popular with character building ​​and good moral habituation. However, there are obstacles in the process of integrating character education, especially in learning Arabic. This program aims to 1) the implementation of community service in character building integration training in Arabic learning, 2) the implementation of assistance in the integration of character education in Arabic learning. The participants of this program are Arabic teachers and 34 students with details of 17 male students and 17 female students. The stages of this program are: 1) the administrative preparation and the delivery information, 2) Presentation and material discussion, 3) training and mentoring, 4) the evaluation. Descriptive analysis was carried to find out the result of this program. The results of the implementation of this community service program are as follows: 1) The character building integration in Arabic learning for teachers and students at MAS Al-Hikmah Bandar Lampung were going very well as indicated by the good enthusiasm and rate of attendance from the participants. and 2) mentoring activities in guiding teachers and students to design Arabic learning integrated with character building are carried out well as indicated by the form of materials, strategies and learning methods that are integrated with character education. Keywords: Integration, character building, learning Arabic.